Migration and Integration: Austrian and California Experiences with Low-Skilled Migrants - Biffl, Gudrun; Martin, Philip L. (Border Crossing, 2018)
This paper examines migrant-integration policies and outcomes in Austria and California, with a special focus on recently arrived low-skilled migrants. Unlike native-born workers, who form a broad diamond shape when arrayed by their level of education to reflect the large share who have completed secondary school but did not earn university degrees, foreign-born workers have more of an hourglass or barbell shape, including some who have more than a first university degree and many who have not completed secondary school. Austria promotes a stepwise approach to the labor market integration of recently arrived refugees, viz, language and skills training before employment, under the theory that investing in people first will raise their long-run earnings. California expects newly arrived migrants to use family and social networks to find jobs and housing to support themselves without government assistance.